TINDAK TUTUR INTEROGATIF DALAM PERCAKAPAN ANAK-ANAK USIA SEKOLAH DASAR - Rosa Dina Monica; Cinta Adinda Nur Jane; Rahmat Prayogi (STKIP Pesisir Selatan, 2025)
This study aims to describe the forms and types of locutionary speech acts used by elementary school children in daily interactions through YouTube videos on the Ueno Family channel. The focus of the study covers three types of locutions, namely declarative locutions, imperative locutions, and interrogative locutions. The method used is a qualitative descriptive approach with the technique of listening and noting to children's speech in three videos: Masak Bareng Ritsuki dan Mama Mega, Main Ular Tangga, and Main dan Belajar Bareng Teman-Teman. The results of the study show that children actively use the three types of locutions in the context of playing, learning, and interacting with parents. Declarative locutions are used to convey information or self-identity, imperative locutions are used to give instructions or requests, and interrogative locutions are used to obtain information or clarification. These three forms of speech reflect the development of children's functional language and show their involvement in active and meaningful social communication. This study provides a real picture of how children use language as a tool for thinking and interacting in everyday life.